FACTORS RELATED NURSE’ JOB SATISFACTION IN WORKPLACE - Nguyen Thai Ngoc , Phong; Nguyen Thi Ngoc , Huong; Nguyen Thi , Thuan; Tran Kim , Quyen (Tạp chí Y Dược Thực hành 175, 2024)
Objective: The aims of study determined the rate of nursing job satisfaction in clinical and its relevant factors at an army hospital in Vietnam. Method: A descriptive cross-sectional study using stratified propotional sampling technique. The research instrument was a self-completed questionnaire following the JSS – version 1 of Paul Spector and using SPSS 13.1. Subject: 383 nurses were working at 38 clinical departments at 175 Military hospital from October 2022 to June 2023. Result: The clinical nurse had high rate of job satisfaction in their career with 45.4% is satisfied, 52.5% is ambivalent, and 2.1% is dissatisfied. Job satisfaction with intention to leave and worktime over forty hours found a correlation. Conclusion: Nurses satisfied with their job (45.4%) and less intention to quit. There is no disparity between nursing job satisfaction levels based on few socio-demographic and occupation-related characteristics.